Konveyor dan Pendinginan dalam Pengasapan Ikan Semi Otomatis: Sebuah Pendekatan Technopreneurship untuk Meningkatkan Kualitas Produk - Ismail, Edy; Alghozi, Haidar Abroru; Sugiyarto, Sugiyarto; Nur, Hamid Ramadhan; Ramadhan, Muhamad Fajar; Abdurahman, Abdurahman; Mulyono, Mulyono; Trisyono, Trisyono (Politeknik Negeri Jakarta, 2025)
The fish smoking industry in Wonosari Village, Demak Regency, produces around 20-25 tons daily, relying on traditional methods that often result in inconsistent quality and compromised hygiene. This study seeks to boost efficiency and product quality by introducing semi-automatic smoking technology powered by technopreneurship principles. The technology integrates conveyor systems and rapid cooling to streamline the smoking process. Using an experimental approach with a technopreneurship twist, the research team collected data through observations, interviews, and prototype testing at Sentra Asap Indah. The testing focused on temperature control, smoking duration, and product quality analysis, including texture, aroma, and food safety. The prototype demonstrated significant efficiency gains, cutting smoking time by 30% and standardizing the process. The rapid cooling system successfully brought the fish temperature down from 80°C to 30°C within 30 minutes, a crucial step in preventing bacterial growth and preserving texture. The overall quality of the smoked fish, in terms of color, taste, and aroma, showed consistent improvement. By integrating conveyor systems for process standardization and rapid cooling for enhanced food safety, this technopreneurship initiative has the potential to increase the competitiveness of local smoked fish products and drive business sustainability.